Rural issues in urban planning: current trends and reflections. Issue 3 (2nd July 2016) - Dandekar, Hemalata C.; Hibbard, Michael
ABSTRACT: While planning has always had an urban emphasis it has also always been concerned with urban–rural linkages and the interactions between urban and rural as well as with the people, economy, and environment of rural places. This symposium issue of International Planning Studies presents recent scholarship on rural planning from around the world.